Improving the Effectiveness of Daycare Education Strategy Through Program Evaluation Using the Context, Input, Process, Product (CIPP) Model - Nurdin Budiyanto; Soewarto Hardhienata; Sri Setyaningsih (Peneliti.net, 2023)
This research aims to describe the strategy for improving the effectiveness of Daycare education through program evaluation using the Context, Input, Process, Product (CIPP) Model. The study adopts an evaluative research method with 10 Daycare centers in Depok City, West Java, Indonesia, as the research subjects. The sampling technique used in this research is purposive sampling. Data collection methods include interviews, questionnaires, observations, and documentation studies. Data analysis techniques involve data collection, reduction, presentation, and conclusion. The research findings are as follows: (1) The evaluation of the context component indicates that the establishment of Daycare Education Institutions does not refer to clear documents issued by the City Education Office; (2) The evaluation of the input component shows that there is generally no specific program for improving the standards of Daycare Educators; (3) The evaluation of the process component reveals that Daycare centers are well-prepared for admitting new students, and all necessary facilities, curriculum, and teachers are well-prepared; (4) The evaluation of the product component shows that Daycare centers have prepared and implemented the learning process according to the established program, but the outcomes for students are not yet evident. The CIPP evaluation model can enhance the effectiveness of Daycare education.